Work Posture Analysis with REBA and RULA Method on Production Operators Repair and Maintenance of LPG 3Kg at PT. XYZ - Aminatus Suhra,; Rachmad Hidayat,; Agung Firdausi Ahsan, (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Wrong posture while working has an impact on productivity. One of them is the operator's work position in the production department at PT. XYZ pays little attention to natural work attitudes and there are activities that have a fairly high ergonomic risk. As a result, complaints such as pain in the legs, shoulders, knees, neck and even the arms occur. At worst, it can lead to long-term sprains and fractures. It is necessary to analyze work posture using the Rapid Entire Body Assessment (REBA) and Rapid Upper Limb Assessment (RULA) methods to determine the level of musculoskeletal hazards and provide improvements to work methods or rearrangement of the work environment. The final score results in the application of REBA and RULA are on the working posture of the both painting sections with scores of 4 and 9, on screen printing on the bottom of the tube scores of 9 and 10, on ring painting results of scores of 10 and 9, on welding results of scores of 7 and 8, and on the installation of seal tape the results of scores 5 and 6 which need to be repaired immediately. Recommendations are given by changing work postures, adding tables and chairs. The operator's attitude and work position are calculated again using the REBA and RULA checksheets. The result is 3 and 3 both painting, 3 and 3 on tube bottom screen printing, 2 and 3 on ring painting, 2 and 3 on welding, 2 and 2 on seal tape installation, which are (acceptable) or acceptable. Keywords: Working Posture Error, REBA, RULA.